STUDI KOMITMEN ORGANISASIONAL: PEKERJA CONTINGENT DAN SURVIVOR - Walani, Fenika (LPPM Universitas Terbuka, 2010)
In recent years, contingent and survivor workers have emerged as a common reality in business activities. Unfortunately, contingent worker has high job insecurity on his employment status. On the other side, downsizing activities can result in decreasing job security of survivor worker. As a consequence, both contingent and survivor workers very potential have low organizational commitment. However, organizations still have an opportunity to give their workers an exclusive treatment for building organizational commitment without ignoring the fact that workers have other commitment foci.